2021
DOI: 10.54203/scil.2021.wvj50
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Respiratory Disease in Broiler Chickens in Egypt during 2020

Abstract: Poultry production has been affected by multiple respiratory diseases triggering serious economic losses in Egypt. The current study aimed to investigate the situation and genetic evolution of respiratory diseases in Egypt during 2020. A total of 53 samples were collected from infected flocks suffering from respiratory signs and variable mortality rates from nine governorates in Egypt during 2020. The collected samples were examined for the detection of respiratory disease viruses (Avian influenza virus (AIV (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The present study has updated the detection rate of HPAI H5N8 in chicken farms in Egypt. The increased ability to distinguish 2019 to 2022 viruses from vaccine strains and the preference for mutations in the HA immunogenic epitopes (R72S, A83D, T140A) are in agreement with the previously mentioned studies by Nabil et al (2020) and Yehia et al (2020 , 2021 ). The identity percentages of the current strains and vaccine used were studied, as exemplified by the rHVT-H5 vaccine (A/mute_swan/Hungary/4999/2006), baculovirus-inactivated H5 vaccine (A/duck/China/E319-2/03) was within the range of 88.8 to 90.7% and H5N2-inactivated vaccine (A/chicken/Mexico/232/1994) was within the range of 75.8 to 76.5%.…”
Section: Discussionsupporting
confidence: 91%
“…The present study has updated the detection rate of HPAI H5N8 in chicken farms in Egypt. The increased ability to distinguish 2019 to 2022 viruses from vaccine strains and the preference for mutations in the HA immunogenic epitopes (R72S, A83D, T140A) are in agreement with the previously mentioned studies by Nabil et al (2020) and Yehia et al (2020 , 2021 ). The identity percentages of the current strains and vaccine used were studied, as exemplified by the rHVT-H5 vaccine (A/mute_swan/Hungary/4999/2006), baculovirus-inactivated H5 vaccine (A/duck/China/E319-2/03) was within the range of 88.8 to 90.7% and H5N2-inactivated vaccine (A/chicken/Mexico/232/1994) was within the range of 75.8 to 76.5%.…”
Section: Discussionsupporting
confidence: 91%
“…The current investigation was conducted in five governorates of the Nile Delta, which have the greatest incidence of outbreaks and the highest occurrence of diseases due to the dense presence of poultry and human activities. In a previous study by Yehia et al , [ 39 ] the prevalence of AI, IB, and ND were 39.6%, 37.7%, and 5.7%, respectively. To calculate the total sample size with 5% accuracy and a 95% confidence level, the prevalence of ND (5.7%) was chosen.…”
Section: Methodsmentioning
confidence: 93%
“…Yehia et al . [ 39 ] reported that AIV subtypes and IBV were recorded in 48 out of 53 farms. A single infection accounted for 90.6% (37.7% I.B., 30.2% H5N8, 9.4% I.B., and 5.7% NDV) ( Table-4 ) The copresence of HPAI (H5N8) and IBV, the unique detection of these coinfected flocks, and LPAI (H9N2) and IBV were detected in 3.8% flocks, as previously reported by El-Shall et al .…”
Section: Discussionmentioning
confidence: 99%
“…The avian in uenza virus (HP, LP), IBV, and NDV were the main detected viruses alone or as coinfected in broiler chickens (32). In recent years, the avian in uenza situation in Egypt has been more complicated due to the detection and circulation of many serotypes, including HPAI (H5N1), HPAI (H5N8), and LPAI (H9N2) (39,40). In the present study the circulation of H5 & H9 subtypes of AIV (5/359) 1.4% could be a risk for emergence of new AI viruses (table 4, Fig3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Yehia, et al (2021) reported that The AIV subtypes and IBV were recorded in 48 out of 53 farms. Single infection represented 90.6% (37.7% I.B, 30.2% H5N8, 9.4% I.B and 5.7% NDV) (table4).…”
mentioning
confidence: 99%